2014
DOI: 10.1111/jnc.12793
|View full text |Cite
|
Sign up to set email alerts
|

SVCT2 transporter expression is post‐natally induced in cortical neurons and its function is regulated by its short isoform

Abstract: Different studies have demonstrated the importance of micronutrients, such as vitamins, for normal adult brain function and development. Vitamin C is not synthesized in the brain, but high levels are detected in this organ because of the existence of specific uptake mechanisms, which concentrate ascorbic acid from the bloodstream to the cerebrospinal fluid and then into neurons and glial cells. Two different isoforms of sodium–vitamin C cotransporters (SVCT1 and SVCT2) have been cloned. SVCT2 expression has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 46 publications
5
32
0
Order By: Relevance
“…It has been shown to negatively regulate the function of the full length transporter by changing its affinity constant via hetero-oligomerization in human embryonic kidney 239T cells and mouse neuronal cells (54). This isoform also had the ability to partially inhibit SVCT1 (54, 55). …”
Section: Sodium-dependent Vitamin C Transportermentioning
confidence: 98%
“…It has been shown to negatively regulate the function of the full length transporter by changing its affinity constant via hetero-oligomerization in human embryonic kidney 239T cells and mouse neuronal cells (54). This isoform also had the ability to partially inhibit SVCT1 (54, 55). …”
Section: Sodium-dependent Vitamin C Transportermentioning
confidence: 98%
“…These findings indicate that SVCT2 is induced during cell arborization and synaptic maturation of deep neurons in the brain cortex. We also identified the expression of a short isoform of SVCT2 (SVCT2sh), which is unable to transport AA and regulate the functional capacity of the active transporter [1]. This finding and its biological consequence in the postnatal brain will be discussed in the following section.…”
Section: Expression and Polarization Of Svct2 During Brain Developmentmentioning
confidence: 99%
“…SVCT2sh was initially thought to be a possible dominant negative of SVCT2 through protein-protein interaction [28]. However, Forster resonance energy transfer (FRET) studies, a decade later using SVCT2-CFP Vitamin Cand SVCT2sh-YFP in the neural linage cell line, N2a [1], showed that the proteins interact at both the intracellular space and the cell membrane. The functional consequence of the interaction reduces the affinity of SVCT2 for its substrate, AA, in neuronal cells, suggesting that SVCT2 activity and intracellular concentrations of AA are tightly modulated during postnatal development in order to generate a precise physiological intracellular dose of AA to trigger the neuronal differentiation and synaptic maturation in a particular period of development.…”
Section: Regulation Of Svct2-mediated Vitamin C Uptake In Neurons By mentioning
confidence: 99%
See 2 more Smart Citations